Dynamic spectrum access enabled home area networks for smart grid communications. (2016) - Bajracharya, Chandra; Rawat, Danda B.
In this paper, we investigate the dynamic spectrum access for home area network in smart grid communications where home appliances access RF spectrum opportunistically. We evaluate the proposed approach through simulations and the numerical results show that the proposed dynamic spectrum access-based smart grid communication outperforms the static spectrum access-based smart grid communications. Smart grid is the transformation of current power grid system through the integration of advanced information technology and communication technology with power system grid. The choice of communication technology for smart grid is highly critical to provide secure, reliable and efficient information transfer between the smart grid components. However, because of dynamic topology changes, connectivity problems, interference and fading issues, and delay requirements, current information and communication infrastructures and standards are incapable of meeting the strict requirements of smart grid technology. The dynamic spectrum access capability of cognitive radio networks is a promising technology that can be used to reduce the communication expenses and improve reliability by improving spectrum utilisation in smart grids.